Abiotic and biotic stress combinations. Issue 1 (11th April 2014) - Suzuki, Nobuhiro; Rivero, Rosa M.; Shulaev, Vladimir; Blumwald, Eduardo; Mittler, Ron
Summary: Environmental stress conditions such as drought, heat, salinity, cold, or pathogen infection can have a devastating impact on plant growth and yield under field conditions. Nevertheless, the effects of these stresses on plants are typically being studied under controlled growth conditions in the laboratory. The field environment is very different from the controlled conditions used in laboratory studies, and often involves the simultaneous exposure of plants to more than one abiotic and/or biotic stress condition, such as a combination of drought and heat, drought and cold, salinity and heat, or any of the major abiotic stresses combined with pathogen infection. Recent studies have revealed that the response of plants to combinations of two or more stress conditions is unique and cannot be directly extrapolated from the response of plants to each of the different stresses applied individually. Moreover, the simultaneous occurrence of different stresses results in a high degree of complexity in plant responses, as the responses to the combined stresses are largely controlled by different, and sometimes opposing, signaling pathways that may interact and inhibit each other. In this review, we will provide an update on recent studies focusing on the response of plants to a combination of different stresses. In particular, we will address how different stress responses are integrated and how they impact plant growth and physiological traits. Contents Summary 32 I. Introduction 32 II. Effects of stress combination on growth, yield and physiological traits in plants and crops 34 III. The complexity of stress response signaling during stress combination 38 IV. Conclusions 39 Acknowledgements 41 References 41